Teaching how to Listen. Blended Learning for the Development and Assessment of Listening Skills in a Second Language - Caruso, Marinella; Gadd Colombi, Anna; Tebbit, Simon (Journal of University Teaching and Learning Practice, 2017)
This paper discusses the integration and effectiveness of blended learning for the development and assessment of listening skills in a second language. The development of oral abilities (listening and speaking) is one of the most challenging and neglected aspects of second language learning (Vandergrift & Goh 2012, Graham & Santos 2015). Listening comprehension work in particular is crucial in the early stages of second language acquisition, and, therefore, for ab-initio language students, for whom processing and decoding auditory input can be very challenging. In 2014 a set of online listening quizzes was created and integrated into two ab-initio Italian courses. The aim was to offer engaging, flexible listening comprehension practice and assessment, which would extend the students’ learning experience, stimulate their learning motivation and allow for a better use of face-to-face teaching in the classroom environment. Having conceptualised listening as a process rather than a product we designed tasks to teach learners how to listen, rather than merely test their comprehension. The validity of the quizzes as a means for the development of listening skills and as a tool for formative and summative assessment was subjected to systematic analysis via an online student survey. The large amount of data collected reveals that the quizzes were a key element in the development of listening skills and the delivery mode did not only meet the students’ learning needs but it was clearly preferred to in-class assessment.